2012
DOI: 10.1002/bsl.2024
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Occurring Disorders in Treatment‐Based Courts: Results of a National Survey

Abstract: Drug courts and mental health courts have expanded rapidly in the past several decades to provide more efficient coordination of treatment and supervision of offenders with behavioral health problems. A significant number of offenders in these court-based programs have co-occurring mental and substance use disorders, which predict early termination, relapse, rearrest, and other negative outcomes. A web-based national survey examined programmatic adaptations for co-occurring disorders (CODs) among 54 drug court… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Although our findings were against prediction, they do fit well with some logic. It is well recognised that SUDs are common among offenders generally (Boden et al, ; Peters et al, ), which is what we also found, but Mafia members are required to appear reliable, maintain power and adhere to the internal representations and principles of their organisation, and such skills tend to be impaired by substance use. It may be that substance misusers would be less likely to be selected for Mafia membership (as they would be viewed as liabilities), and if selected by chance, their involvement would be short lived.…”
Section: Discussionsupporting
confidence: 79%
“…Although our findings were against prediction, they do fit well with some logic. It is well recognised that SUDs are common among offenders generally (Boden et al, ; Peters et al, ), which is what we also found, but Mafia members are required to appear reliable, maintain power and adhere to the internal representations and principles of their organisation, and such skills tend to be impaired by substance use. It may be that substance misusers would be less likely to be selected for Mafia membership (as they would be viewed as liabilities), and if selected by chance, their involvement would be short lived.…”
Section: Discussionsupporting
confidence: 79%
“…For those with gambling problems, a gambling treatment court (GTC) could be modelled after the more general practice of problem-solving courts, where clients with psychiatric or substance use problems are redirected away from prison into a therapeutic situation in which the emphasis is on rehabilitation rather than punishment (Cooper, 2003;Farrell, 2011;Nolan, 2002;Peters, Kremling, Bekman, & Caudy, 2012;Slinger & Roesch, 2010).…”
Section: Diversion To Problem-solving Courtsmentioning
confidence: 99%
“…Managing behavioral health needs as well as securing housing, transportation, and employment upon release are all challenging. This population has high rates of recidivism and homelessness and tends to have limited social and financial supports (Messina, Burdon, Hagopian, & Prendergast, 2004;Peters, Kremling, Bekman, & Caudy, 2012;Peters, Sherman, & Osher, 2008).…”
mentioning
confidence: 99%